The Phenomenon of Learning Motivation of Elementary School Students - Edu, Ambros Leonangung; Jaya, Petrus Redy P.; Ni, Laurentius (International Journal of Elementary Education, 2021)
Learning motivation is one of the important things that can affect the student's learning process. This study aims to explore the phenomenon of learning motivation of elementary school students. This research is quantitative research using survey exploratory research. Subjects involved in this study amounted to 51 elementary school students. Data collection uses a questionnaire as a data collection instrument. The questionnaire was compiled based on four components of learning motivation, namely the drive for achievement, discipline in learning, readiness to overcome difficulties, and curiosity. The questionnaire uses a Likert scale with the categories "always", "often", "sometimes", and "never". The data collected were analyzed using descriptive statistics. The results showed that in general, the students had high motivation. However, this high motivation is not in line with concrete actions that show their enthusiasm for learning. This is because the motivation that develops is extrinsic. Students learn to get rewarded or to avoid punishment from teachers. Nevertheless, the students are aware of their obligations as students and believe in their abilities. This can be used as initial capital to encourage students to improve their learning achievement.